1984
DOI: 10.1128/aem.47.6.1255-1260.1984
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Study of Methane Oxidation in Lake Washington

Abstract: The distribution of methane and methane-oxidizing bacteria in the water column of Lake Washington was determined monthly for 1 year. The methane profiles were relatively constant, with little stratification and low concentrations (0.05 to 0.5 ,uM). The number of methane-oxidizing bacteria detected by a filter-plating method was routinely <1/ml throughout the water column, and no incorporation or oxidation of methane was detected by radioisotopic labeling, even after methane was added. However, samples taken fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
58
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(70 citation statements)
references
References 9 publications
11
58
1
Order By: Relevance
“…Methanotrophic bacterial production has rarely been reported, and therefore we rely on total methane-oxidation estimates for comparison with previous studies. Individual measurements of methane oxidation in this study, ranging from 0.01 to 39 mg C·m 3 ·d Ϫ1 , are in line with previously reported estimates of methane oxidation in lakes (0-207 mg C·m 3 ·d Ϫ1 ; Jannasch 1975, Rudd and Hamilton 1975, Harrits and Hanson 1980, Lidstrom and Somers 1984, Bédard and Knowles 1997, Striegl and Michmerhuisen 1998, Utsumi et al 1998). Regarding depth-integrated estimates, Rudd and Taylor (1980) and Striegl and Michmerhuisen (1998) used bottle incubations to monitor methane concentration change over time, and reported lake-area specific methane oxidation to be 10-700 mg C·m Ϫ2 ·d Ϫ1 .…”
Section: Methane Concentrations and Bacterial Activitiessupporting
confidence: 92%
See 1 more Smart Citation
“…Methanotrophic bacterial production has rarely been reported, and therefore we rely on total methane-oxidation estimates for comparison with previous studies. Individual measurements of methane oxidation in this study, ranging from 0.01 to 39 mg C·m 3 ·d Ϫ1 , are in line with previously reported estimates of methane oxidation in lakes (0-207 mg C·m 3 ·d Ϫ1 ; Jannasch 1975, Rudd and Hamilton 1975, Harrits and Hanson 1980, Lidstrom and Somers 1984, Bédard and Knowles 1997, Striegl and Michmerhuisen 1998, Utsumi et al 1998). Regarding depth-integrated estimates, Rudd and Taylor (1980) and Striegl and Michmerhuisen (1998) used bottle incubations to monitor methane concentration change over time, and reported lake-area specific methane oxidation to be 10-700 mg C·m Ϫ2 ·d Ϫ1 .…”
Section: Methane Concentrations and Bacterial Activitiessupporting
confidence: 92%
“…84,No. 4 M (Rudd and Hamilton 1978, Harrits and Hanson 1980, Lidstrom and Somers 1984, Liu et al 1996, Bédard and Knowles 1997, Striegl and Michmerhuisen 1998, Utsumi et al 1998. Both this range and the methane concentration profiles reported correspond well with our results (Fig.…”
Section: Methane Concentrations and Bacterial Activitiessupporting
confidence: 92%
“…There are results suggesting the existence of more than one reaction center in particulate MMO [35], yet in both pure cultures and sediment, Michaelis Menten kinetics have been observed [10,36,37]. The Vma x values determined in this study were in the upper range of Vm~ , values reported in the literature [6,37,38]. The S0.…”
supporting
confidence: 50%
“…2). The K m for 0 2 between 20 and 37/zM 0 2 [38,39] allows at least half maximal velocity with respect to oxygen only in the top 1 mm sediment layer. For CH 4 oxidation with respect to both 02 and CH4, the layer with at least half maximal velocity is probably even thinner.…”
mentioning
confidence: 99%
“…The K, value for methane uptake (1.6 PM) is slightly lower than previously reported values. K, values reported for methane consumption by soils and sediments range from 2.5 for a landfill cover soil [ 151 and 2.2 to 3.7 for a Danish Wetland [ 131 to 8.3 to 10.7 for Lake Washington sediments [33]. Yavitt et al [3] reported K, = 3.7 to 42.0 pmol I_ , peat from intact peat cores of a West Virginia bog.…”
Section: Discussionmentioning
confidence: 99%